2018
DOI: 10.1159/000495500
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Glasgow Prognostic Score or Modified Glasgow Prognostic Score for Patients with Colorectal Cancer Receiving Various Treatments: a Systematic Review and Meta-Analysis

Abstract: Background/Aims: Increasing evidence indicates that the systemic inflammatory response plays a vital role in carcinogenesis. The Glasgow Prognostic Score or modified Glasgow Prognostic Score (GPS/mGPS) is a novel inflammatory indicator which consists of CRP and albumin. Here, we performed a meta-analysis to evaluate the prognostic value of the GPS/ mGPS in patients with colorectal cancer (CRC) and to assess its consistency in different CRC therapies. Methods: The electronic databases PubMed, Embase, Scopus, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Principally based on this basic evidence, recent studies focused on the prognostic value of several blood markers and their various combinations including the platelet to lymphocyte ratio, neutrophil to lymphocyte ratio, Glasgow prognostic score and its modified form, systemic immune-inflammation index, and PNI. [29][30][31][32][33][34][35] Before its wide acceptance as an immunonutritional marker in many cancers including the NPC, the PNI was first utilized by Onodera et al in 1984 for prediction of postoperative complication risks in gastrointestinal cancers. 25 Although the low PNI values below various cutoffs have been almost consistently demonstrated to be strongly linked with poorer clinical outcomes in patients with NPC, yet most such studies were highly heterogeneous with regards to the disease stages and treatment modalities, and unfortunately focused on just 1 or 2 survival end points.…”
Section: Discussionmentioning
confidence: 99%
“…Another biomarker that correlates with inflammatory responses is albumin. Albumin levels also positively correlate with survival in cancer patients [15].…”
Section: Introductionmentioning
confidence: 94%
“…The systemic inflammation has an impact on the phenotype of cellular components of the tumour microenvironment and affects levels of cytokines. C-reactive-protein (CRP) levels are regulated by several proinflammatory cytokines and the activity of infiltrating immune cells [14,15]. Another biomarker that correlates with inflammatory responses is albumin.…”
Section: Introductionmentioning
confidence: 99%